Case Study: Problems and Solutions for Learning to Read and Write the Qur'an at TPQ Al-Huda, Darat Sawah Village, Seginim District. - Midela Eka Putri; Asmara Yumarni; Giyarsi (PT. Islamic Research Publisher, 2024)
The study of the Qur'an is a fundamental obligation for every Muslim, playing an important role in shaping religious character from an early age. This research explores the problems and solutions in learning to read and write the Qur'an at the Al-Qur'an Education Park (TPQ) Al-Huda, Darat Sawah Village, Seginim District, South Bengkulu Regency. The main focus of this research is to analyze the learning process, identify the obstacles faced, and develop effective solutions to improve the quality of education in TPQ. The methodology used is qualitative descriptive research with a case study approach. The research subjects consisted of the head of TPQ, educators, students, guardians of students, and students. Data is collected through observation, in-depth interviews, and documentation, then analyzed through data reduction techniques, data presentation, and conclusion drawn. The data credibility test was carried out by extending participation, diligent observation, triangulation of methods, and data sources. The results of the study showed various problems in learning to read and write the Qur'an, including the difficulty of students in understanding the material, lack of family support, low interest in learning religion, the number of materials taught, monotonous teaching methods and media, limited facilities and infrastructure, and the lack of quality of teachers. The solutions identified include more attention from teachers, memorization at home, giving supportive assignments, variations in teaching methods, support from the government, counseling on the importance of religious knowledge to the community, regular meetings with students' parents, providing motivation to students, and teacher coaching or training. This research contributes significantly to the field of education by providing in-depth insights into the challenges and solutions in learning to read and write the Qur'an. This finding is expected to be a reference for other TPQs and similar educational institutions in an effort to improve the effectiveness and quality of Qur'an education in Indonesia. The results of the study also emphasize the importance of collaboration between teachers, families, and the government in creating a conducive and sustainable learning environment.